Measuring coffee yields: A comparison of one-time harvest and allometric methods - Hoffmann, Vivian; Kagezi, Godfrey; Rwakazooba, Ezra; Zane, Giulia (International Food Policy Research Institute, 2019)
Measuring yields accurately is critical for evaluating the impact of interventions that aim to increase ag-ricultural productivity. Self-reported survey data may be subject to social desirability bias, especially in the context of intervention-based studies. Further, farmers participating in training programs may put more effort into measuring their yield because they are interested in learning whether the new practices are effective, which could systematically bias their self-reports, compared to those of farmer not offered training. Therefore, it is often argued that field measurements such as crop cuttings and weighing are required for accurate measurement. In this note, we assess the suitability of allometric measurement for use in the context of large-scale data collection on coffee yields. We compare allometric yield estimates of Robusta coffee grown by smallholder farmers in Uganda with those obtained through a one-time harvest of both ripe and unripe cherries of a specified minimum size at the beginning of the fruiting season.